The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1002/jor.1100050302
|View full text |Cite
|
Sign up to set email alerts
|

Experimental vascularized bone grafts: Histopathologic correlations with postoperative bone scan: The risk of false‐positive results

Abstract: A positive bone scan in an experimental model of bilateral ulna diaphyseal bone grafts demonstrated early bone repair in both vascularized and nonvascularized orthotopic ulna autografts. A positive bone scan did not correlate with the perfusion of the vascularized and nonvascularized grafts as measured by microangiograms done 1 week postoperatively. In this model, if the bone scan is intended to monitor the circulatory status and viability of the bone graft, it must be done earlier than 1 week postoperative pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 9 publications
(8 reference statements)
0
9
0
1
Order By: Relevance
“…Vascularized bone grafts (VBGs) are capable of achieving primary bony healing without creeping substitution and can, thus, hasten fracture healing, and, revascularize ischemic bone. 3,12,13 Other potential advantages are faster rates of incorporation, greater durability, and increased viability by increasing blood supply to nonunion site. Several methods of transferring a VBG to the scaphoid have been reported in the literature.…”
mentioning
confidence: 98%
“…Vascularized bone grafts (VBGs) are capable of achieving primary bony healing without creeping substitution and can, thus, hasten fracture healing, and, revascularize ischemic bone. 3,12,13 Other potential advantages are faster rates of incorporation, greater durability, and increased viability by increasing blood supply to nonunion site. Several methods of transferring a VBG to the scaphoid have been reported in the literature.…”
mentioning
confidence: 98%
“…Negative scan results were found to be associated with the later occurrence of complications (non-union, osteomyelitis) or total graft failure, while positive scan results correlated with uncomplicated graft healing. In animal experiments it has been shown that a positive scintigram later than 1 week after surgery does not necessarily indicate an intact blood supply; rather it may also be due to new bone formed by creeping substitution on the surface of a graft whose major portion is not viable [4,21,22]. Nevertheless, negative scan results obtained later than 1 week (up to 6 weeks) after surgery in patients who received revascularized grafts have been found always to be associated with complications [2,23].…”
Section: Discussionmentioning
confidence: 94%
“…15,16 Surrounding necrotic bone may even be revascularized and recolonized by osteocytes from the circulation provided by the graft. 15,16 Techniques that introduce living vascularized bone provide an excellent option for difficult-to-treat fractures in regions with poor local blood supply such as the scaphoid proximal pole or waist fractures with proximal pole avascular necrosis. 11Y13 pollicis brevis to treat a scaphoid waist fracture.…”
mentioning
confidence: 99%
“…14 As circulation and viable osteoclasts and osteoblasts are maintained, healing may be accelerated. 15,16 Vascularized grafts may provide replacement for deficient bone with less resorption and loss of structural integrity than traditional bone grafting. 15,16 Surrounding necrotic bone may even be revascularized and recolonized by osteocytes from the circulation provided by the graft.…”
mentioning
confidence: 99%
See 1 more Smart Citation